Thermomechanical Model and Bursting Tests to Evaluate the Risk of Swelling and Bursting of Modified 9Cr-1Mo Steel Steam Generator Tubes during a Sodium-Water Reaction Accident - C. Bertrand; A. Allou; F. Beauchamp; E. Pluyette; P. Defrasne; F. Baqué (Science and Technology of Nuclear Installations)
The MECTUB code was developed to evaluate the risk of swelling and bursting of Steam Generator (SG) tubes. This code deals with the physic of intermediate steam-water leaks into sodium which induce a Sodium-Water Reaction (SWR). It is based on a one-dimensional calculation to describe the thermomechanical behavior of tubes under a high internal pressure and a fast external overheating. The mechanical model of MECTUB is strongly correlated with the kind of the material of the SG tubes. It has been developed and validated by using experiments performed on the alloy 800. A change to tubes made of Modified 9Cr-1Mo steel requires more knowledge of Modified 9Cr-1Mo steel behavior which influences the bursting time at high temperatures (up to 1200°C). Studies have been initiated to adapt the mechanical model and to qualify it for this material. The first part of this paper focuses on the mechanical law modelling (elasticity, plasticity, and creep) for Modified 9Cr-1Mo steel and on overheating thermal data. In a second part, the results of bursting tests performed on Modified 9Cr-1Mo tubes in the SQUAT facility of CEA are used to validate the mechanical model of MECTUB for the Modified 9Cr-1Mo material.